Evaluation of condylar flattening in dentate and non-dentate patients using panoramic radiography - Cantor Mora, Anthony (2020)
Introduction: Morphological alterations of the condyles are determined by a decrease of bone tissue in the mandibular condyle, changing its shape and size. One of the most frequent signs of these alterations involves condylar flattening that occurs among dynamic processes and is characterized by a loss of convexity of the articular condyle. Radiographically this is observed as a convex surface, the condylar bone cortex is continuous and there is an absence of irregular radiopaque or radiolucent areas. Objectives: To evaluate the radiographic characteristics of condylar flattening of the temporomandibular joint in dentate and non-dentate patients using panoramic radiography. Methods: We evaluated panoramic radiographs obtained at the D3RX Oral and Maxillofacial Digital Radiology Center in Floridablanca-Colombia from January 2017 to December 2018. Patients were randomly selected according to fulfillment of the following inclusion criteria: availability of panoramic radiographs showing the entire condylar structure of male and female patients aged 18 to 70 years attending from January 2017 to December 2018. This number of radiographs was defined according to a database. We evaluated the presence of flattening, the shape and the affected side and sex. The Chi-square test was applied. P <0.005. Results: A total of 520 panoramic radiographs were obtained; 260 from dentate patients and 260 from non-dentate patients. Patient characteristics show that edentulous patients had a higher incidence of alterations in the shape, side and type of flattening in the panoramic radiographs. Edentulous patients have a higher incidence of presenting some alteration in their shape, side and flattened condyles observed in panoramic radiographs in 51.2% versus 35.1% of dentate patients (P <0.001). Conclusions: The morphological changes of the condyles observed in panoramic radiographs were more prevalent in women than men, with a higher incidence in rounded condyles and greater involvement in edentulous patients. The results of this study show that although panoramic radiography is not considered the best tool to determine the presence of slight morphological changes at the level of the jaw, it can be used as the first diagnostic aid to obtain an overview of not only the temporomandibular joint but also other anatomical and dental structures that should be studied in disorders of the temporomandibular joint.